Sustainable Futures in Southern Africa's Mountains Multiple Perspectives on an Emerging City - Membretti, Andrea; Taylor, Sue Jean; Delves, Jess L. (Sustainable Development Goals Series, 2023)
This open access book presents multiple disciplinary perspectives on the challenges and opportunities for sustainable development in the South African mountain city of Phuthaditjhaba. These challenges are embedded in the complex environmental, socio-cultural and political contexts of the region. Established as the capital of the QwaQwa 'homeland' under Grand Apartheid, this city is now home to between 400,000 - 700,000 people but in many areas lacks formal infrastructure and services. Each chapter of this volume addresses a different aspect of the city's development and all take the UN Sustainable Development Goals as a common framework to guide their reflections on potential sustainable futures for Phuthaditjhaba. While the circumstances in Phuthaditjhaba will be familiar to many researchers of informal and growing cities in developing regions, the mountain setting of the city brings its own set of challenges and opportunities linked to the rugged and steep terrain, remoteness and natural resources. This book serves to showcase the diverse research taking place in this emerging mountain city and provide reflections on how a sustainable future can be ensured for its environment and inhabitants.